Pengaruh Penggunaan Mobile Banking dan Potensi Risiko Terhadap Kepercayaan Nasabah dengan Literasi Keuangan sebagai Variabel Moderasi - Nur Amalia, Syahamah; Pratiwi, Annisa Rizki; Gultom, Parapat (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study uses financial literacy as a moderating variable to investigate how potential harms associated with mobile banking affect customer trust. The quantitative descriptive approach is the methodology used, and data were collected through questionnaires filled out by approximately 308 respondents. SmartPLS 3.0 software will then be used to analyze the data using partial least squares. According to the study findings, customer trust is positively and significantly influenced by the variable of mobile banking usage, positively and significantly influenced by potential risks, positively and significantly influenced by financial literacy, and positively and significantly influenced by potential risks. The impact of mobile banking on customer trust cannot be reduced by the variable of financial literacy. The potential threats to customer trust cannot be reduced by the variable of financial literacy. The variable of customer trust can cover 59.5% of the independent variables, according to the results of the R Square test, and the remaining 40.5% in other studies using other variables. Keywords: Mobile Banking Usage, Potential Risks, Customer Trust, Financial Literacy